Fabrication and characterization of Nd:YAG transparent ceramic - Ho, Favian Shu Wei (2018)
Solid state laser ceramics was discovered in the 1960s and through the advancement of technology, there is a rapid demand for a variety of applications. With several developments and milestones in the laser field, there are more interest of research in using transparent ceramics for light emitting diode (LED). The use of solid-state materials in laser technology is based on doping yttrium aluminium garnet (YAG) ceramics with rare earth elements with an +3 oxidation state. In this project, 0.3 - 1at% neodymium-doped YAG (Nd:YAG) was fabricated by solid state reaction method using commercial raw powders. The fabrication processes were outlined and some characterization methods were used to study the transmission efficiency and microstructure. The results allowed for comparison of different doping concentration that was more ideal for properties of Nd:YAG transparent ceramic. The type and amount of dopant concentration will affect the result of the emission from laser medium, leading to wide range of applications. However, there are many factors such as additives, sintering parameters and experimental methods that might possibly affect the outcome of the final product being discussed in this report.